Disruption of planetary system architectures by stellar flybys - Przyłuski, Robert; Rickman, Hans; Wajer, Paweł; Wiśniowski, Tomasz; Turrini, Diego; Polychroni, Danae; Danielski, Camilla; Kruijssen, J. M. Diederik; Longmore, Steven; Chevance, Mélanie (Universe, 2025)
We investigate the survivability of solar system-like planetary systems during close encounters in stellar associations using a suite of 1980 N-body s...
Online veröffentlicht: 22. Juli 2025
Gesehen am 12.01.2026